Implementation of the indoor navigation algorithm based on bluetooth low energy 4.0. technology - Овсянников, Александр Александрович; Новиков, Павел Андреевич (Computer Tools in Education, 2015)
Some of the indoor-navigation implementational wireless models are described in this article. Algorythms, based on basic models, are proposed. Based on data from the beacons the impact of other wireless connections is analyzed.